1794 Pa. Laws 764, An Act Providing For The Inspection of Gunpowder chap. 337 - (:unkn) unknown (My University, 1794)
Required gunpowder intended for sale in Philadelphia to be sold in "good and tight" kegs of varying weights, quality timber,at least twelve hoops, a hole bored, and marked on the barrel. Powder shall be inspected using a pendulum powder proof.
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER